Tondano Pyroclastic - M.T. Zen; Muziel Alzwar (Institute for Research and Community Services (LPPM) ITB, 1974)
Abstract. Recent A recent investigation into the volcanic geology of Minahasa revealed the existence and distribution of pyroclastic flow sheets of which origin and mode of emplacement are yet to be solved. These pyroclastic flow sheets are found covering nearly whole Minahasa. It consists of loose to dense tuff or tuffaceous material, containing angular, to subangular and rounded pumice fragments measuring from a few mm to 15-20 mm across, showing several cycles of deposition. Welding is only detected at one spot and very limited. Quartz fragments are common but not abundant. Along the lake of tondano those pyroclastics form terraces ranging in height from 1.5 to 20 m, whereas farther away along the North and the South east these pyroclastic sheets form typical soft undulating landscapes. Most probably these pyroclastics originated from fissure like eruptions in a longitudinal riftvalley on the crest of the Minahasa geanticline bordered to the SE by the slightly crescentic Lembean scarp, and to the NW by a row of young volcanoes. Some of the pyroclastics might have deposited aerially some showed some indication of flowage after deposition. In Central and East Minahasa most part of these pyroclastic sheets are covered by young and recently produced volcanics of andesitic composition. The magnitude of this deposit makes it necessary to be mapped as a separate unit and the regional mapping team of the Geological Survey of Indonesia should pay considerable attention to their presence and geologic importance, since, next to Toba this pyroclastic deposit is one having the largest surface distributionRingkasan. Suatu penelitian pendahuluan di daerah Minahasa baru-baru ini menemukan penyebaran suatu batuan pyroklastika secara luas sekali. Batuan ini dapat digolongkan sebagai